2020
DOI: 10.1055/s-0040-1713169
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Damage of the Portal Vein is Associated with Heparin-Like Effect in Advanced Stages of Cirrhosis

Abstract: Background Portal vein thrombosis (PVT) is the most common thrombotic complication in cirrhosis; however, local risk factors involved in its pathogenesis are still not fully investigated. The aim of the study was to evaluate hemostasis and endothelial damage in the portal vein in patients with cirrhosis and portal hypertension. Methods Adult cirrhotics undergoing transjugular intrahepatic portosystemic shunt were consecutively enrolled. Rotational thromboelastometry (ROTEM), dosage of total circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 55 publications
0
54
4
2
Order By: Relevance
“… 24 ROTEM ® was performed according to the standard protocols supplied by the manufacturer, as previously reported. 25 , 26 , 27 The following tests were performed: INTEM (to assess intrinsic coagulation pathway), EXTEM (to assess extrinsic coagulation pathway) and FIBTEM (to assess fibrinogen contribution to clot formation and stability). For EXTEM and INTEM tests, the following ROTEM ® parameters were collected: clotting time (CT), clotting formation time (CFT), maximum clot firmness (MCF), α‐angle and maximum lysis for EXTEM and INTEM tests.…”
Section: Methodsmentioning
confidence: 99%
“… 24 ROTEM ® was performed according to the standard protocols supplied by the manufacturer, as previously reported. 25 , 26 , 27 The following tests were performed: INTEM (to assess intrinsic coagulation pathway), EXTEM (to assess extrinsic coagulation pathway) and FIBTEM (to assess fibrinogen contribution to clot formation and stability). For EXTEM and INTEM tests, the following ROTEM ® parameters were collected: clotting time (CT), clotting formation time (CFT), maximum clot firmness (MCF), α‐angle and maximum lysis for EXTEM and INTEM tests.…”
Section: Methodsmentioning
confidence: 99%
“…32 Moreover, the observation of a significantly higher concentration of microparticles of endothelial origin (CD62E-MP) in the portal vein compared to the systemic circulation suggested greater endothelial damage at this level. 33 Although all these arguments make it possible that local inflammatory conditions could play a role in PVT development in patients with cirrhosis, this has not been demonstrated in prospective cause-effect studies.…”
Section: Local Portal Vein Alterationsmentioning
confidence: 99%
“…Additionally, a small RCT showed that TIPS is more effective than EVL and NSBBs in preventing rebleeding in patients with cirrhosis and portal vein thrombosis, with a higher rate of thrombus resolution but without differences in mortality [61]. Patients with cirrhosis and portal vein thrombosis, which is the most common thrombotic complications in cirrhosis [86][87][88], may be a third group in which to consider TIPS earlier rather than later in the setting of secondary prophylaxis. This would be particularly important if the patient is awaiting liver transplantation, as the presence of thrombosis at time of transplantation is associated with a higher risk of post-transplant mortality [89].…”
Section: Second Line Therapymentioning
confidence: 99%